Quantifying the Long-Term Economic Benefits of European Electricity System Integration - Eva Schmid; Brigitte Knopf (Fondazione Eni Enrico Mattei (FEEM), 2014)
This paper analyses a set of model-based decarbonization scenarios in order to quantify the long-term economic benefits that arise from an increasing integration of the pan-European electricity system. It thereby focuses on the interplay between transmission infrastructure and renewable generation capacity expansion. We confirm earlier findings that, on aggregate, pan-European transmission capacity expansion constitutes a no-regret option for integrating increasing shares of variable renewables in mitigation scenarios with positive social returns on investment. However, it turns out that the change in total discounted system costs that occurs as transmission capacity expansion increases is modest in magnitude, with a maximum of 3.5% for a case with no expansion compared to one with massive expansion. In technical terms this means that the optimum is rather flat and that taking into account regional and local benefits and distributional aspects, could alter the evaluation of the economic benefits considerably. A crucial finding in this context is that the configuration of pan-European transmission infrastructure and the importance of specific country-connections, i.e. a Southern versus a Northern solution, crucially hinges on the relative development of specific investment costs for solar and wind technologies over the next decades.
Keywords: Q42; Q48; Q54; 330; Transmission Infrastructure Planning; European Energy Policy Targets; Mitigation